Analysis of Shopee Driver Partner Satisfaction Service on the Shopeefood Driver Application with the End User Computing Satisfaction Method (EUCS) - Parwadi, Parwadi; Sofa, Maya (Information Technology and Systems, 2024)
This study aims to analyze shopee driver partner satisfaction with the shopeefood driver application using the End User Computing Satisfaction (EUCS) method. The EUCS method is used to measure driver partner satisfaction with the shopee food driver application using 5 variables, namely content, accuracy, format, ease of use and timelines. So that the level of satisfaction from shopeefood driver application users is more measurable, so as to generate input for the developer. This study was conducted by taking a sample of 100 drivers. The results showed that all factors simultaneously had an influence on user satisfaction. But in itself only the accuracy and timeliness factors have a significant effect because it is necessary to improve and improve these factors because these factors are very important in influencing user satisfaction of the shopeefood driver application. while using the End User Computing Satisfac method